Bredia bullata (Melastomataceae), a new species from limestone areas in Yunnan, China - Zeng, Si-Jin; Tong, Yi-Hua; Xia, Nian-He (Phytotaxa, 2022)
A new species, Bredia bullata, from China, is described and illustrated based on morphological and molecular evidence. This new species is morphologically similar to B. malipoensis in having tomentose stems and leaves, cordate leaf blades in unequal pairs, an umbellate inflorescence, and undulate petals with an unguiculate base and retuse apex, but differs by having bullate leaf blades, white hypanthia and elliptic calyx lobes. Our phylogenetic analysis using the plastid genome strongly supports the generic placement of B. bullata and B. malipoensis within Bredia.